A new color pattern of the Bungarus candidus complex (Squamata: Elapidae) from Vietnam based on morphological and molecular data - Nguyen, Sang Ngoc; Nguyen, Vu Dang Hoang; Nguyen, Thang Quoc; Le, Ngan Thanh Thi; Nguyen, Luan Thanh; Vo, Ba Dinh; Vindum, Jens V.; Murphy, Robert W.; Che, Jing; Zhang, Ya-Ping (Zootaxa, 2017)
Kraits with black and white bands from Nui Chua National Park, central Vietnam are morphologically similar to the Burmese Krait, Bungarus magnimaculatus, however, analysis of molecular data finds them to be nested within the B. candidus complex.